2021
DOI: 10.1039/d1sc02197d
|View full text |Cite
|
Sign up to set email alerts
|

An amplification-free ultra-sensitive electrochemical CRISPR/Cas biosensor for drug-resistant bacteria detection

Abstract: An amplification-free electrochemical CRISPR/Cas biosensor utilizing silver metallization (termed E-Si-CRISPR) allows detection of methicillin-resistant Staphylococcus aureus (MRSA) with excellent sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 42 publications
(56 reference statements)
0
50
0
Order By: Relevance
“…Although the RAA-Cas12a method we established has high sensitivity and specificity, it still has several weaknesses. First, our method does not detect the few MRSA strains containing the mecA-like gene (mecC) (Lakhundi and Zhang, 2018), which has also been observed in other molecular strategies (Buchan et al, 2015;Xu et al, 2020;Suea-Ngam et al, 2021). mecC is a new resistance gene recently discovered and identified in MRSA isolated from animals.…”
Section: Discussionmentioning
confidence: 89%
“…Although the RAA-Cas12a method we established has high sensitivity and specificity, it still has several weaknesses. First, our method does not detect the few MRSA strains containing the mecA-like gene (mecC) (Lakhundi and Zhang, 2018), which has also been observed in other molecular strategies (Buchan et al, 2015;Xu et al, 2020;Suea-Ngam et al, 2021). mecC is a new resistance gene recently discovered and identified in MRSA isolated from animals.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, most of the studies reported the LoD in CFU/mL, of which seven studies showed LoD of 1 CFU/mL. Five studies reported the LoD in molarity [ 12 , 17 , 18 , 28 , 38 , 39 ]. Of these, CAS-EXPAR for the detection of Listeria monocytogenes showed the lowest LoD up to the attomolar level [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that our model and assay design principles may be broadly applicable to other detection methods such as those which rely on electrochemical impedance measurements for target detection. [23][24][25] Fig. 4.…”
Section: Discussionmentioning
confidence: 99%